MOTIVATION GUEST SERVICE AGENT IN CONDUCTING UP SELLING IN FRONT OFFICE DEPARTMENT TO INCREASE REVENUE AT HILTON GARDEN INN BALI - I Wayan Ade Ardiana; I Gusti Agung Mas Krisna Komala Sari; Ni Nyoman Sri Astuti (Politeknik Negeri Bali, 2020)
This research discussed about the motivation of guest service agents in conducting upselling using Maslow's theory hierarchy of needs. This research aims to find out what are the motivations of Guest Service Agents in conducting upselling conducted at the Front Office Department at Hilton Garden Inn Bali and to find out how much motivation Guest Service Agent in conducting upselling programs to increase hotel revenue at the Hilton Garden Inn Bali. The data collection methods used in this study are questionnaires, interviews, observation, documentation and literature study methods. The researcher used simple descriptive statistical data analysis techniques, in this research to calculate the mean and percentage. Results of the respondent's questionnaire answers, tabulation of data, calculating percentages, looking for the dominant variable from Maslow's theory and interpreting the results. The results of the research showed that the main needs are social needs with a total value of 20.87%. The second is the self esteem needs with a total value of 20.78%. The third is self-actualization needs with a value of 20.60%. The fourth is safety needs with a value of 20.47% and the fifth is physiological needs with a total value of 17.29%, so these five needs are motivated by guest service agents in conducting upselling at Hilton Garden Inn Bali hotels so they can increase revenue at Hilton Garden Inn Bali hotels every month.